Reproductive biology of striped snakehead, Channa striata (Bloch, 1793) in Lake Rawa Pening, Central Java - Djumanto Djumanto; Atik Murjiyanti; Nuravida Azlina; Aisyah Nurulitaerka; Anissa Dwiramdhani (Jurnal Iktiologi Indonesia, 2019)
The striped snakehead (Channa striata Bloch, 1793) is the top predator fish found in Lake Rawa Pening and other freshwaters. Its population was declining due to very high fishing pressures, habitat quality decreases, and other fac-tors. The aim of this study was to examine the condition factor and fecundity of snakehead in Lake Rawa Pening. Fish sampling was carried out monthly from October 2017 to August 2018, using fish fence made from bamboo blinds operated by local fishermen. Total length, individual body weight, stage of gonadal maturity (MS), gonadal weight, and oocytes diameter of fish samples were measured. Fish condition factor, gonado somatic index (GSI), oocyte diameter, fecundity, and the size of first maturity of fish were determined. There were 409 individuals snakehead fish collected consisting of 138 females and 271 males. Fish length ranged from 234-646 mm (males) and 242-648 mm (females). The average of the condition factor (K) of male ranged from 0.778 to 0.923, while in female ranged from 0.826 to 0.929. The relationship between the length-weight of male and female was isometric. The percentage of female snakehead that reached MS I; II; III; IV was 15.6; 27.0; 37.4; 20.0%, respectively. The GSI ranged from 1.52 to 3.54. Oocyte diameter ranged from 0.5 to 1.7 mm with an average of 1.2 mm. Fecundity ranged from 2,843-23,230 eggs with an average of 9,167 eggs. The female snakehead was predicted to reach the first sexual maturity at a total length of 315 mm. Abstrak Ikan gabus (Channa striata Bloch, 1793) merupakan ikan predator puncak yang ditemukan di Danau Rawa Pening dan perairan tawar lainnya. Keberadaan populasinya semakin menurun disebabkan oleh tekanan penangkapan yang sangat tinggi, kualitas habitat semakin menurun, dan oleh faktor lainnya. Tujuan penelitian ini adalah untuk mengkaji faktor kondisi dan reproduksi ikan gabus di Danau Rawa Pening. Pengambilan sampel ikan dilakukan setiap bulan dari Oktober 2017 hingga Agustus 2018 menggunakan perangkap yang terbuat dari kirai bambu dan jaring. Ikan gabus yang dikumpulkan sebanyak 409 ekor yang terdiri atas 138 betina dan 271 jantan. Panjang ikan contoh berkisar antara 234-646 mm (jantan) dan 242-648 mm (betina). Parameter yang diukur meliputi panjang total, bobot individu, tingkat kematangan gonad, berat gonad, dan diameter oosit. Faktor kondisi, indeks kematangan gonad, fekunditas, dan ukuran pertama matang gonad ditentukan. Faktor kondisi rata-rata pada ikan jantan berkisar antara 0,778 hingga 0,923; sedangkan ikan betina berkisar antara 0,826-0,929. Hubungan panjang-bobot ikan jantan dan betina adalah isometrik. Persentase ikan gabus betina yang mencapai TKG I; II; III; IV masing-masing adalah 15,6; 27,0; 37,4; 20,0% dengan indeks kematangan gonad berkisar antara 1,52 hingga 3,54. Ukuran diameter oosit berkisar antara 0,5 hingga 1,7 mm dengan rata-rata 1,2 mm. Adapun fekunditas berkisar antara 2.843-23.230 telur dengan rata-rata 9.167 telur. Ukuran ikan gabus betina saat kali pertama dewasa seksual diperkirakan pada panjang total 315 mm.